PENGAWASAN PEMERINTAH KOTA PEKANBARU TERHADAP JALUR ANGKUTAN BARANG TAHUN 2024 - Hasibuan, Aminah Rahmah; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The regulation of routes and operating hours for freight transportation in Pekanbaru City is a policy of the local government to maintain smooth traffic flow, road user safety, and road infrastructure conditions. However, many freight vehicles are still found to violate route and operating hour regulations, causing congestion, road damage, and traffic accident risks. This study aims to examine the supervision of the Pekanbaru City Government over freight routes in 2024. This study uses a qualitative research method with a descriptive approach. Data collection techniques are conducted through interviews, documentation, and literature studies. This study uses Siagian's supervision theory, which includes direct supervision, indirect supervision, preventive supervision, and repressive supervision. The research results indicate that direct supervision is carried out through the placement of officers, patrols, and internal evaluations, but it is hindered by a lack of consistency in field supervision. Indirect supervision is implemented through the use of CCTV/ETLE, periodic reports, as well as the involvement of the police and the community, although community reporting has not been running optimally. Preventive supervision is conducted through socialization, education, installation of prohibition signs, and KIR tests, but the socialization has not been evenly distributed. Meanwhile, repressive supervision is carried out through warnings, fines, and administrative sanctions, but law enforcement has not been maximized. Keywords: Supervision, Freight Transport Routes, Pekanbaru City